Utlization of cavendish banana in the production of catsup - Momville, Marie Karen Tabucan
The general objective of the study was to use Cavendish banana for catsup production. The study consisted of three phases. The first phase dealt with the determination of the most acceptable banana catsup formulation. From the results, of the sensory evaluations and data analyses, the most acceptable formulation was with the addition of spices. The banana catsup had a medium red color and had a moderately strong banana flavor. It was moderately thick and moderately sweet. Overall, it was rated as like moderately. The second phase was concerned with the quality assessment of the preferred banana catsup. Physico-chemical tests were done on the Cavendish banana and the banana catsup. Most of the results were within the range set for the raw material and the finished product. The banana catsup underwent Total Plate Count (TPC) and Yeast and Mold Count (YMC) analyses after storage at 8°C and 37°C. He results was <10 cfu/g at both temperatures. The third phase involved the cost analysis of the banana catsup. The banana catsup had a selling price of P19.68 per 240 g bottle. Comparison with a leading banana catsup brand was not made because of the difference in the packaging material used.